Teachers’ and Proprietors’ perception of pre-primary school curriculum process in Ife-East Local Government Area of Osun State, Nigeria - Victoria Ihekerenma, Iroegbu (Advances in Social Sciences Research Journal, 2019)
This study investigated preprimary school teachers’ and proprietors’ perception of curriculum process in preprimary education in Nigeria. 140 teachers/proprietors from private preprimary schools were purposively selected for the study. The research instrument was a 32 item researcher constructed curriculum process questionnaire in the Likert format with Cronbach’s Alpha of .852. The items were distributed into five sections: impending curriculum sensitization; curriculum objectives; contentment; methods and strategies; and methods of evaluation. The instrument was administered on the teachers and proprietors in their various schools and collected by the researcher and assistants on the same day. The resulting data were analyzed using the Chi Squared statistics. The results showed that in 28 cases out of 32, the Chi squared obtained was not significant at the .05 level. It was concluded that preprimary school teachers and proprietors had similar perceptions of preprimary curriculum process. It was recommended that preprimary school teachers and proprietors be given regular on-the-job training in this regard.